2018
DOI: 10.4103/ijn.ijn_256_16
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical presentation and correlative histopathological patterns in renal parenchymal disease

Abstract: Suspicion and subsequent detection of renal disease is by an assessment of the urinalysis and renal function in the clinical context. Our attempt in this study is to correlate initial presenting features of urinalysis and renal function to the final histopathological diagnosis. A retrospective analysis of 1059 native kidney biopsies performed from January 2002 to June 2015 at Amrita Institute of Medical Sciences was conducted. Correlative patterns between urinalysis, renal function, and final histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
5
2
Order By: Relevance
“…To date, there are only few clinical studies focusing on patients with subnephrotic proteinuria upon biopsy proven nephropathies. In line with our study, recently published biopsy cohorts comprised about 50% of cases with subnephrotic proteinuria (53% versus 44.77% and 47.6%) [20,21]. Histological results in this studies showed that IgAN is most frequent (20.9% and 35.4%) in the group of subnephrotic patients similar to our results [20,21].…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…To date, there are only few clinical studies focusing on patients with subnephrotic proteinuria upon biopsy proven nephropathies. In line with our study, recently published biopsy cohorts comprised about 50% of cases with subnephrotic proteinuria (53% versus 44.77% and 47.6%) [20,21]. Histological results in this studies showed that IgAN is most frequent (20.9% and 35.4%) in the group of subnephrotic patients similar to our results [20,21].…”
Section: Plos Onesupporting
confidence: 92%
“…In line with our study, recently published biopsy cohorts comprised about 50% of cases with subnephrotic proteinuria (53% versus 44.77% and 47.6%) [20,21]. Histological results in this studies showed that IgAN is most frequent (20.9% and 35.4%) in the group of subnephrotic patients similar to our results [20,21]. In detail, the frequency of following diagnosis differed from our study.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…In abstract no. 22 for “Poster Presentations” titled “A study on prevalence of sleep disturbance and factors affecting it in CKD-5 patients on maintenance hemodialysis”, published on pages 28-122, supplement issue 1, volume 28 of Indian Journal of Nephrology,[1] the list of authors and affiliations is incorrectly written as “Avinash Ignatius, Shubhangi Jagtap-Karmakar, Avinash Ignatius, Suresh Sankar; Department of Nephrology; DaVita Care Pvt Ltd.; Bengaluru; Karnataka; India”. The correct list of authors and their affiliations should read as “Shubhangi Jagtap-Karmakar, Avinash Ignatius, Suresh Sankar; Department of Nephrology, Noble Hospital Pune”.…”
mentioning
confidence: 99%
“…In abstract no. 96 for “Poster Presentations” titled “Role of Copeptin Assay as an Improved Diagnostic Tool of Hypotonic Polyuria”, published on pages 28-122, supplement issue 1, volume 28 of Indian Journal of Nephrology,[1] the list of authors and affiliations is incorrectly written as “Sameer S Deshmukh, Kaustubh S Chaudhari, Sameer S Deshmukh, Nishant R Tiwari, Rohan S Sharma; Department of Nephrology, University of Oklahoma Health Sciences Center, Oklahoma, USA”. The correct list of authors and their affiliations should read as “Kaustubh S Chaudhari, Sameer S Deshmukh, Nishant R Tiwari, Rohan S Sharma; Department of Internal Medicine, University of Oklahoma Health Sciences Center, Oklahoma; USA”.…”
mentioning
confidence: 99%